TRANSFORMATION OF ORGANIZATIONAL CULTURE AND ITS IMPACT ON PERFORMANCE: A SYSTEMATIC REVIEW IN THE CONTEXT OF GLOBAL UNCERTAINTY - Umar Hamdani; Salsabila Citra Devi; Aisya Ramadhani Eka Aprildianti; Sopiah (RADJA PUBLIKA, 2026)
In the face of escalating global uncertainty, organizations are required not merely to survive but to adaptively transform their cultures to sustain performance. Agile and flexible organizational culture is positioned as a strategic instrument in responding to the complexity and ambiguity of the business environment. This study aims to systematically review the relationship between organizational culture transformation, performance, and the context of global uncertainty based on literature from the past five years. A Systematic Literature Review (SLR) approach was adopted using the PRISMA 2020 guidelines, covering 39 articles from the Scopus database. The analysis was conducted using descriptive, thematic, and content-based approaches. The findings indicate that organizational culture plays a strategic role as a mediator in coping with external pressures and in driving organizational performance. This review also reveals methodological and conceptual gaps, and proposes a future research agenda emphasizing the importance of digital integration, cross-cultural approaches, and longitudinal studies. The primary contribution of this study lies in asserting the position of organizational culture as a strategic lever in building adaptive performance amid global dynamics.